Iran's Experience of Health Cooperatives as a Public-Private Partnership Model in Primary Health Care: A Comparative Study in East Azerbaijan - Mostafa Farahbakhsh; Homayoun Sadeghi-Bazargani; Alireza Nikniaz; Jafar Sadegh Tabrizi; Akram Zakeri; Saber Azami (Tabriz University of Medical Sciences, 2012)
Background: Iran started a new public-private partnership model in form of health coopera-tives which is somehow different from other types of health cooperatives throughout the world. In this study we compared the performance and quality of health services in public health cen-ters (PHCs) and cooperative health centers (CHCs).Methods: In this comparative study performance quality of two cohorts of public and coopera-tive health centers were compared in several health service delivery programs over the time pe-riod of 2001- 2002.Results: Screening program: the rate of visited population during screening program was higher in CHCs. Maternal health care program: In some of studied programs CHCs had better results. Child health care: Most indicators were better or similar in CHCs. School health program and Health education: All indices were better or similar in CHCs. Environmental health: population based positive function was not significantly different for the population covered by CHCs compared to population covered by PHCs. Management: Client and staff satisfaction as well as participation and attitudes of personnel towards management was better in CHCs. Mean annual cost per capita of the covered population by PHCs was higher.Conclusion: CHCs as a public private partnership model in Iran may deliver preventive health care services as effective as PHCs in many fields and even better in some areas.